Sistem Informasi Manajemen Pegawai Berbasis Desktop (Studi Kasus: LPP RRI Jayapura) - Heru Sutejo (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2023)
Human Resources Management Information System (HRMIS) is a critical element in organizations or institutions to ensure the efficiency and effectiveness of employee data management. This research discusses the development of a desktop-based HRMIS at LPP RRI Jayapura to overcome challenges in employee data processing, such as the lack of user understanding of the existing system and issues in personnel administration. The research method used is the waterfall approach with steps including requirement analysis, system design, implementation, and testing. The research location focuses on the HR and General Affairs department of LPP RRI Jayapura. Data collection is done through observation and interviews with the Head of the Administrative Division. The results of the research include system design, database table structure, user interface, and black box testing. This system features the management of job positions, ranks, employees, spouses, children, promotion, mutation, and report generation. Black box testing indicates that the system functions well. The conclusion of this research is that the development of a desktop-based HRMIS can improve the efficiency and effectiveness of employee data management at LPP RRI Jayapura. This system is expected to provide solutions to existing challenges and enhance the performance of personnel management in the institution.